2013
DOI: 10.1371/journal.pone.0073254
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in SELE Gene and Risk of Coal Workers' Pneumoconiosis in Chinese: A Case-Control Study

Abstract: BackgroundCoal workers' pneumoconiosis (CWP) is characterized by chronic pulmonary inflammation and fibrotic nodular lesions that usually lead to progressive fibrosis. Inflammation is the first step in the development of CWP. E-selectin, an adhesion molecule, is involved in the development of various inflammatory diseases.MethodsWe investigated the association between the functional polymorphisms in SELE and the risk of CWP in Han Chinese population. Three polymorphisms (T1880C/rs5355, T1559C/rs5368, A16089G/r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Lee et al suggested that high serum levels of interleukin 8 in Korean subjects were associated with CWP and those of serum tumour necrosis factor α were associated with the progression of CWP at the 1-year follow-up [ 38 ], but not at the 3-year follow-up [ 39 ]. In addition, studies of Chinese CWP cases revealed associations between CWP and genetic polymorphisms related to inflammatory markers such as E-selectin [ 40 ] or the inflammasome (nod-like receptor protein 3) [ 41 ]. Combining these previous data with the findings of the current investigation, it is logical to hypothesize that long-term CDE can instigate the inflammation response and damage arterial walls, which leads to atherosclerosis and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al suggested that high serum levels of interleukin 8 in Korean subjects were associated with CWP and those of serum tumour necrosis factor α were associated with the progression of CWP at the 1-year follow-up [ 38 ], but not at the 3-year follow-up [ 39 ]. In addition, studies of Chinese CWP cases revealed associations between CWP and genetic polymorphisms related to inflammatory markers such as E-selectin [ 40 ] or the inflammasome (nod-like receptor protein 3) [ 41 ]. Combining these previous data with the findings of the current investigation, it is logical to hypothesize that long-term CDE can instigate the inflammation response and damage arterial walls, which leads to atherosclerosis and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…SELE , a member of selectin family, usually expressed on activated platelets and endothelial cells, exerts its effects in lymphocytes and monocyte recruitment, rolling, and diapedesis to the inflammatory areas 60 , 61 . Previous studies have demonstrated that SELE is associated with coronary artery disease 62 , coronary heart disease 63 , coal workers' pneumoconiosis 64 , hypertension 65 and colorectal cancer 66 . However, there was currently no research on SELE gene associated with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…No genomic markers, however, have been validated to date . This includes potential susceptibility loci from genome‐wide association studies (GWAS, rs73329476, rs4320486 and rs117626015), and the T1559C/rs5368 polymorphism . Regarding TNF‐α, the TNF‐α‐308A allele has been linked to ever having CWP especially with nodules as opposed to PMF, whereas TNF‐α promoter TNF2 polymorphism has been associated with the development of large opacities .…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…1 This includes potential susceptibility loci from genome-wide association studies (GWAS, rs73329476, rs4320486 and rs117626015), 51 and the T1559C/rs5368 polymorphism. 52 Regarding TNF-α, the TNF-α-308A allele has been linked to ever having CWP especially with nodules as opposed to PMF, 53 whereas TNF-α promoter TNF2 polymorphism has been associated with the development of large opacities. 54 Other identified polymorphisms include IL-4 C-590T; 55 cyclo-oxygenase-2 rs689466 and rs20417; 56 microRNA-149 rs2292832 TT; 57 a potentially protective effect of MMP3 rs522616 GG; 58 and NLRP3 rs1539019, especially in early disease.…”
Section: Genetic Testing and Genomic Biomarkersmentioning
confidence: 99%